2005
DOI: 10.1007/s10389-005-0120-3
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic situation and health outcomes of single parents

Abstract: Objective: Individualization and pluralization of lifestyles have led to a continually growing number of one-parent families (lone parents) in the Federal Republic of Germany. In 2003, there were approximately 2.4 million lone parents with children living in Germany. Over 80% of lone parents are women. The objective of this review is to summarize the scientific evidence concerning health outcomes and socioeconomic conditions of lone parents. Methods:We performed a structured literature review to identify relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
4
11
0
Order By: Relevance
“…These findings are also consistent with the majority of the relevant studies [40]. Significant associations were also observed with either depressive symptoms or worse self-assessed level of health and educational level, employment status, family income, single family status and children age [38, 41, 42]. …”
Section: Discussionsupporting
confidence: 90%
“…These findings are also consistent with the majority of the relevant studies [40]. Significant associations were also observed with either depressive symptoms or worse self-assessed level of health and educational level, employment status, family income, single family status and children age [38, 41, 42]. …”
Section: Discussionsupporting
confidence: 90%
“…Such phenomena, which the present study found in South Korea, are in line with previous studies in Western countries (Benzeval 1998;Neises and Grüneberg 2005;Westerling 2006, 2007;Young et al 2005), suggesting that lone mothers seem to be more vulnerable to socioeconomic disadvantages and poor social support than are their partnered counterparts.…”
Section: Discussionsupporting
confidence: 82%
“…Second, we did not include several important variables associated with poorer health, such as unhealthy behaviors (e.g., smoking tobacco, drinking alcohol, irregular exercise/ eating habits, and taking pain-killers/psychotropic drugs), body mass index, physical/mental problems, and low social capital, because these factors were not available for assessment (Curtis 2001;Wang 2004;Westin and Westerling 2007;Young et al 2005). Neises and Grüneberg (2005) performed a structured literature review across the European Union and reported that lone mothers suffer more frequently from these risk behaviors and problems. Therefore, the findings of this study cannot be interpreted directly in terms of the association between lone mothers and 'poor/fair' health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Belzeval, 1998; Chen, Ryan-Henry, Heller, & Chen, 2001; Neises & Gruneberg, 2005; Waters et al, 2000). Despite extensive research documenting poor psychological outcomes facing parents raising children with delayed development, little research has examined these parents’ physical health.…”
Section: Physical Well-being Among Mothers Of Children With Delayed Dmentioning
confidence: 99%